Religious offences in common law Asia: colonial legacies, constitutional rights and contemporary practice - Thio, Li-Ann (Constitutionalism in Asia, 2021)
Orthodoxy, order and odium : the enduring legacy of religious penal clauses in contemporary Asia / Li-ann Thio and Jaclyn L Neo -- Religious penal clauses in Commonwealth Asia : a brief history / Kevin YL Tan -- Apollonian restraint and dionysian impulse : law, freedom and religious feelings / Li-ann Thio -- Making Islamic penal clauses : translation, transformation and transmogrifycation / Arif Jamal -- Between religious coexistence and religious hierarchy : divergent developments in religious offence laws in common law Asia / Jaclyn L Neo -- Religious penal clauses in India / Mrinal Satish -- Forbidden discourse : evaluating the transformation of colonial-era religious penal offences into contemporary Pakistan's Blasphemy Laws / Syed Ali Raza -- Bangladesh : public law, religious freedom and regulating 'religious sentiment' / SM Masum Billah -- Prosecuting religious violence in Sri Lanka / Mario Gomez -- Offences against religion in Malaysia : navigating the 'secular' federal constitution and the salience of Islam in the constitutional order / Dian AH Shah -- Religious offences penal clauses and the Singapore constitutional order : secular, sensible but sensitive to the sacred? / Li-ann Thio -- Recalibrating the scales of criminal justice in Brunei Darussalam : Religious Penal Clauses 1905-2018 / Ann Black.